In Search of Russian Modernism - Livak, Leonid (Book collections on Project MUSE., 2018)
The writing and teaching of Russian literary and cultural history has changed little since the 1980s. In Search of Russian Modernism challenges the basic premises of Russian modernist studies, removing the aura of certainty surrounding the analytical tools at our disposal and suggesting audacious alternatives to the conventional ways of thinking and speaking about Russian and transnational modernism. Drawing on methodological breakthroughs in Anglo-American new modernist studies, Leonid Livak explores Russian and transnational modernism as a story of a self-identified and self-conscious interpretive community that bestows a range of meanings on human experience. Livak's approach opens modernist studies to integrative and interdisciplinary analysis, including the extension of scholarly inquiry beyond traditional artistic media in order to account for modernism's socioeconomic and institutional history. Writing with a student audience in mind, Livak presents Russian modernism as a minority culture coexisting with other cultural formations while addressing thorny issues that regularly come up when discussing modernist artifacts. Aiming to open an overdue debate about the academic fields of Russian and transnational modernist studies, this book is also intended for an audience of scholars in comparative literary and cultural studies, specialists in Russian and transnational modernism, and researchers engaged with European cultural historiography.